A fibre flexure shear model for seismic analysis of RC-framed structures. - Ceresa, P.
While currently existing modelling approaches of reinforced concrete (RC) behaviour allow a reasonably accurate prediction of flexural response, the determination of its shear counterpart needs further developments. There are various modelling strategies in the literature able to predict the shear response and the shear?flexure coupling under monotonic loading conditions. However, very few are the reported models that have demonstrated successful results under cyclic loading, as in the seismic load case. These considerations lead to this research work focused on the development of a flexure?shear model for RC beam?column elements. A reliable constitutive model for cracked RC subjected to cyclic loading was implemented as bi-axial fibre constitutive model into a two-dimensional Timoshenko beam?column element. Aim of this research work is to arrive at the definition of a numerical model sufficiently accurate and, at the same time, computationally efficient, which will enable implementation within a finite element package for nonlinear dynamic analysis of existing non-seismically designed RC structures that are prone to shear-induced damage and collapse.
Keywords: Fibre element; Shear deformations; Seismic analysis; Reinforced concrete frames